Velocity of sound of binary mixture R507 and ternary mixture R404A - Avsec, J.; Marcic, M.; Leipertz, Alfred; Fröba, Andreas Paul (Journal of Thermophysics and Heat Transfer, 2003)
The development of mathematical models for calculation of the velocity of sound and other thermodynamic functions of state for the refrigerant mixtures R507 and R410A is discussed. For the calculation of the thermodynamic functions of state, the perturbation theory with the Lennard-Jones (12-6) potential was used as reference. A model is presented for the calculation of-the influence of multipolar, induction, and dispersion interactions. Multipolar interactions are calculated up to octopole moment. All important contributions (translation, rotation, internal rotation, vibration, intermolecular potential energy, and influence of electron and nuclei excitation) are featured. The analytical results are compared, with experimental data and models obtained by classical thermodynamics and show quite good agreement. Experimental data have been obtained by dynamic light scattering.